The effectiveness of task-based and project-based language teaching in improving speaking - Asuan, Asuan (CAHAYA PENDIDIKAN, 2023)
A quasi-experimental research had been conducted to test the effectiveness of using TBLT and PBLT in improving eighth-grade students’ speaking skill at Maitreyawira Junior High School in Batam. The researcher used pre-test and post-test with non-equivalent group design. Two classes (8H and 8I) that consist of 30 students in each class were chosen. The control class was taught by using TBLT and the experimental class was taught by using PBLT. The data were analyzed by paired and independent t-test. The results showed that there was a significant difference in the students’ speaking skill. The sig-value in the control class was 0.001. There was also a significant difference in the students’ speaking skill with the sig-value of 0.000 in the experimental class. Both sig-values were lower than 0.05. Moreover, the students’ speaking scores were higher than before the treatment whether in control class or experimental class. It was proven by the improvement of 4.50 of the mean score in the control class, and the improvement of 5.86 of the mean score in the experimental class. Therefore, TBLT and PBLT were recommended to be used in teaching English, especially in teaching speaking in order to improve students’ speaking skill.